The effects of Onychectomy (Declawing) on forearm and leg myology in a Kinkajou (Potos flavus) - Martens, Lara L. (2024)
Recently, onychectomy, the “declaw” surgery in which all or part of the distal phalanges are removed, has been shown to have significant effects on the forearm muscles of felids. While this surgery should clearly affect the limb muscles (especially those that insert on the removed or modified bone), these effects have not been studied beyond felids or in the hindlimb. To that end, we herein evaluated the muscle architecture of a kinkajou (Potos flavus) that was declawed on all four of its limbs and compared its anatomy to that of intact specimens and the felid findings. As expected, some of the declawed kinkajou’s muscles were substantially different from those of the intact specimens, and as was seen in felids, its digital muscles appear to have been weaker. However, unlike in the felids, the declawed kinkajou had relatively larger forearm muscles. Also, contrary to expectation, the leg muscles of the declawed kinkajou were not substantially different, perhaps reflecting important differences in limb use. Future analyses should examine this anatomy in other declawed kinkajou specimens and also look at the effects of this surgery in other taxa, for instance, non-arboreal relatives of the kinkajou as well as other arboreal taxa.